What is predatory publishing and what impact it has - CUCIUREANU, Gheorghe (Journal of Social Sciences)
The article explores the phenomenon of predatory publishing, an increasingly debated topic in the scientific community, with a particular focus on its impact in the Republic of Moldova. Predatory publishing is defined as journals and conferences that exploit researchers through false promises of rapid review and indexing, without meeting academic standards. They prioritize profit over scientific quality and integrity, leading to the publication of low-quality research and the dissemination of misinformation. The impact of this is significant, affecting the integrity of research, the credibility of science and the global academic economy. In the Republic of Moldova, where research resources are limited, publication in such journals jeopardizes scientific development, wasting financial and human resources and negatively affecting international collaborations. In order to combat this phenomenon, education and strict regulations on scientific publishing are needed, especially for young researchers who are often victims of this type of practice.